Prevalence and clinical characteristics of Crooke’s cell adenomas in 101 patients with T-PIT-positive pituitary adenomas: Case series and literature review - Zhu, Dimin; Wang, Zongming; Tian, Tian; Wu, Xinyi; He, Dongsheng; Zhu, Yonghong; Liu, Dawei; Wang, Haijun (Frontiers in Endocrinology, 2022)
Purpose: We aimed to perform a retrospective analysis of a rare subtype of corticotroph adenoma, Crooke's cell adenoma, to better understand its clinical features. Methods: We collected T-PIT-positive pituitary adenomas and screened Crooke’s cell adenomas from January 2020 to December 2021 in our center. Case reports of such tumors were also collected through a literature search. Clinical data such as biochemical tests, imaging examinations, and pathological data of the above cases were analyzed. Results: A total of 101 T-PIT-positive patients were treated in our center in the last 2 years, and 4 were finally pathologically diagnosed with Crooke’s cell adenomas. All of these patients were male with elevated adrenocorticotropic hormone levels, and 50.0% presented with hypercortisolemia, Cushing's syndrome, visual impairment, and headache. The tumor diameter was significantly larger in these 4 patients (37.0 mm) than in the other patients (26.0 mm), and their tumor invasive behavior was more pronounced. Cases reported in the literature were mainly female (72.8%), and the clinical presentation was also dominated by Cushing's syndrome (65.1%) and hormonal dysfunction. Tumors were more common as macroadenomas (33.2 mm) and suprasellar growths (63.8%). The tumor recurrence rate was as high as 55.6%, with 6 cases progressing to pituitary carcinomas and 7.7% of tumor-related deaths. Our further integrated analysis of our center and reported cases revealed that gender, Cushing's syndrome, visual dysfunction, hormonal disorders, and tumor growth characteristics were statistically different in different tumor categories. Conclusion: Crooke’s cell adenoma is a tumor subtype with obvious clinical aggressive behavior, and an in-depth analysis of its clinical characteristics may assist in developing a comprehensive treatment plan.